2017
DOI: 10.1016/j.chemgeo.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of lead silicate glasses and melts

Abstract: To cite this version:Ilyes Ben Kacem, Laurent Gautron, Daniel Coillot, Daniel R. Neuville. Structure and properties of lead silicate glasses and melts. Chemical Geology, Elsevier, 2017, 461, pp.104-114 AbstractViscosity, density and glass transition temperature measurements were performed on the simple PbO-SiO 2 system with increasing PbO content from 5 to 70 mol.%. The results of these analyses have been complemented by spectroscopic studies (Raman & X-Ray Absorption Spectroscopy) in order to link macroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 52 publications
2
48
0
4
Order By: Relevance
“…Low-frequency range (<1200 cm −1 ) of the Raman spectrum contains the bands typical for the siloxane bonds. The band at 139 cm −1 can be attributed to the boson peak of the SiO2 network [16]. The bands at 450 and 559 cm −1 correspond to Si-O-Si symmetric stretching of Q4 and Q3 species, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Low-frequency range (<1200 cm −1 ) of the Raman spectrum contains the bands typical for the siloxane bonds. The band at 139 cm −1 can be attributed to the boson peak of the SiO2 network [16]. The bands at 450 and 559 cm −1 correspond to Si-O-Si symmetric stretching of Q4 and Q3 species, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…In the trigonal pyramid structure, there are two bridging oxygen sites and one non-bridging oxygen (NBO) which is a Te = O double bond [5,16,25]. This is a unique structural characteristic of TeO 2 glass, distinct from other network-forming glasses; e.g., silicates, phosphates and germanates in which only the NBO and bridging oxygen exist as a part of the structural unit [5,16,[26][27][28][29]. Modifiers such as BaO and ZnO break the random network of glasses, and the concentration of TeO 3 and TeO 3?d units increases [30].…”
Section: Introductionmentioning
confidence: 99%
“…Pb-silicate glasses have unique optical properties that make them suitable for high-end 'crystal glass' tableware, as well as for industrial applications in radiation shielding or in optoelectronic devices (Kohara et al, 2010). A complete structural description of the PbO-SiO 2 system by Raman and X-ray absorption spectroscopies can be found in the work by Ben Kacem et al (2017). These authors showed that the addition of only 5 mol% PbO resulted in a significant decrease of viscosity and that glass transition temperature decreased continuously with increasing PbO contents, concluding that Pb had considerable network-modifying potential even at low concentrations.…”
Section: Melting Point and Structure Of Molten Pbsiomentioning
confidence: 99%